2014
DOI: 10.1021/ie4041115
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Enhanced Solubilization and Simultaneous Degradation of Phenanthrene in Marine Sediment by Electro-Fenton Treatment

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are one of the main types of contaminants entering the coastal marine environment. Therefore, when polluted sediments are dredged, they should be remediated for beneficial use. Numerous methodologies can be applied to remove these hydrophobic substances from solid matrixes. Among them, the use of surfactants shows a potential application on solubilizing organic pollutants. In this work, critical micelle concentration (cmc) studies of synthetic nonionic surfactants such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Various surfactants are now frequently applied in contaminated sites remediation for desorption and transferring pollutants from soil phase into the water phase, which definitely influenced the following remediation step for target pollutants removal (Besha, Bekele, Naidu, & Chadalavada, 2018;Iglesias, Sanromán, & Pazos, 2014;Mao, Jiang, Xiao, & Yu, 2015;Mulligan, Yong, & Gibbs, 2001;Panizza et al, 2013;Wang, Hoag, Collins, & Naidu, 2013;Ying, 2006). In this study, the frequently used surfactants, namely Tween 80, Triton X-100, and Brij 35, are selected, and their properties are listed in Supporting Information Table S3 (Iglesias et al, 2014).…”
Section: The Influence Of Surfactants On Btex Degradationmentioning
confidence: 99%
“…Various surfactants are now frequently applied in contaminated sites remediation for desorption and transferring pollutants from soil phase into the water phase, which definitely influenced the following remediation step for target pollutants removal (Besha, Bekele, Naidu, & Chadalavada, 2018;Iglesias, Sanromán, & Pazos, 2014;Mao, Jiang, Xiao, & Yu, 2015;Mulligan, Yong, & Gibbs, 2001;Panizza et al, 2013;Wang, Hoag, Collins, & Naidu, 2013;Ying, 2006). In this study, the frequently used surfactants, namely Tween 80, Triton X-100, and Brij 35, are selected, and their properties are listed in Supporting Information Table S3 (Iglesias et al, 2014).…”
Section: The Influence Of Surfactants On Btex Degradationmentioning
confidence: 99%
“…In recent years, many studies have been carried out on the solubilization of PAHs by surfactants [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Aryal et al reported that a single surfactant solution above CMC can enhance the solubility of phenanthrene (Phe) and pyrene (Pyr) in water, and the solubility was linearly proportional to the surfactant concentration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in droplet size was attributed to the relatively sufficient surfactant concentration to decrease the oil-water interfacial tension, cover the ZBEO droplets, and prevent the droplet coalescence [11,23,37]. On the other hand, the increasing in droplet diameter at higher Tween 40 levels can be attributed to the appearance of micelles, which promoted the depletion flocculation when droplet size was relatively large; however, this effect can be hampered once the droplet dimension below a certain level [7,38]. Based on these results and in connection with the aim of this study, the optimum SOR was 5:5 for further experiments.…”
Section: Effect Of Surfactant Concentrationmentioning
confidence: 99%
“…On the other hand, the surface tension values became constant in the presence of TS, which could be attributed to the saturation of surfactant concentration. Above a particular surfactant concentration, called critical micelle concentration (CMC), the surfactants begin to form self-assembled micelles and surface tension values becomes almost constant [38].…”
Section: Influence Of Ts On the Zbeo Nanoemulsions Formationmentioning
confidence: 99%